2013
DOI: 10.1039/c2fo30229b
|View full text |Cite
|
Sign up to set email alerts
|

The protective effect of menhaden oil in the oxidative damage and renal necrosis due to dietary choline deficiency

Abstract: Weanling rats fed a choline-deficient diet develop kidney oxidative damage, tubular and cortical kidney necrosis, renal failure and animal death. The effect of dietary menhaden oil was assayed on the mentioned sequence correlating oxidative stress with renal structure and function. Rats were fed ad libitum 4 different diets: (a) a choline-deficient diet with corn oil and sunflower hydrogenated oil as a source of fatty acids; (b) the same diet supplemented with choline; (c) a choline-deficient diet with menhade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 27 publications
(48 reference statements)
0
6
0
Order By: Relevance
“…Total reactive antioxidant potential TRAP is a measure of hydrosoluble molecules. In kidney of CD rats, its value decrease from day 0 to 7 25,26 . Higher values of antioxidant enzymes were found in Wistar rats fed fish oil diets 27 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Total reactive antioxidant potential TRAP is a measure of hydrosoluble molecules. In kidney of CD rats, its value decrease from day 0 to 7 25,26 . Higher values of antioxidant enzymes were found in Wistar rats fed fish oil diets 27 .…”
Section: Discussionmentioning
confidence: 99%
“…Menhaden oil, which is a very important source of ω3 fatty acids, has a notorious protective effect 20,25 .…”
Section: Discussionmentioning
confidence: 99%
“…Some data have suggested that choline attenuates oxidative stress in patients with asthma [ 17 ]. A previous study reports that the dietary choline could induce the oxidation [ 20 , 21 ] of lipid component in the membranes of muscle cells and also affected the intracellular lipid metabolism [ 22 ]. Therefore, this underlines the importance of choline-rich foods for proper muscle function.…”
Section: Introductionmentioning
confidence: 99%
“…9 In recent studies, it has been shown that methionine and choline deficiency (MCD), both separately and in combination may induce oxidative stress in various tissues and organs such as liver, kidney, and brain. [10][11][12][13] Alpha-lipoic acid (LA) is well know antioxidant, and has ROS scavenging capacity, the capacity to regenerate endogenous antioxidants such as glutathione, and vitamins E and C, and a metal chelating capacity. Besides, LA is both water and lipid soluble and therefore can cross biological membranes easily, such as blood-brain barrier, and performs its antioxidant action both in the cytosol and in the plasma membrane.…”
Section: Introductionmentioning
confidence: 99%